2016
DOI: 10.2500/ajra.2016.30.4343
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Illness: A Systematic Review of Depression in Chronic Rhinosinusitis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 30 publications
(110 reference statements)
3
83
0
Order By: Relevance
“…We estimated the prevalence of depression to be about 21% in CRS patients which is in line with other studies that used HADS questionnaire and reported the prevalence of 11-23.8% [11]. The main reason of this wide range in these studies can be related to different HADS cut-off points used by them.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We estimated the prevalence of depression to be about 21% in CRS patients which is in line with other studies that used HADS questionnaire and reported the prevalence of 11-23.8% [11]. The main reason of this wide range in these studies can be related to different HADS cut-off points used by them.…”
Section: Discussionsupporting
confidence: 87%
“…In a cohort study in 2011 the incidence of depression in patients with CRS was 77% more than control group with a hazard ratio of 1.56 [8] while these studies report depression as a highly prevalent disorder in CRS patients there are some other studies which report the prevalence of highly probable depression as low as 3 to 4% [9,10]. In 2016 Schloser et al reviewed 13 studies and reported the prevalence of probable depression to be from 11 to 40% [11]. Considering this wide range of results and the fact that causality in this association is not yet understood, it seems necessary to conduct more studies in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Although it varied slightly depending on the method of diagnosis (i.e., physician diagnosed, PHQ, HADS, BID), the overall frequency International Archives of Otorhinolaryngology was significant, ranging from 18 to 40% of patients with CRS. 4 Given this opportunity to improve care for patients with increased risk of comorbid psychiatric illness, we sought to determine the knowledge, attitudes and practices of ARS members in the evaluation and management of MDD in patients with chronic rhinosinusitis. The ARS was chosen as a representative body of otolaryngologists who have a clinical emphasis or interest in the care of patients with rhinologic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if this is a causative relationship; however it appears likely that co-existing depression results in both higher rates of symptom reporting and amplifies symptom severity, particularly in CRSsNP (103) . Patients with co-existing depression report poorer disease specific health related quality of life both before and after treatment for CRS (104) . Although treatment for CRS has been shown to reduce depression scores, there is no evidence on whether treatment of depression may result in improvement of CRS-related QOL.…”
Section: Management Of Individuals With Recalcitrant Crs Is Based Onmentioning
confidence: 99%